Managing in Tough Times: Downsized — Maintaining Your Access to Health Care - Michael S. Gutter; Selena Garrison (EDIS)
FCS7238, a 3-page fact sheet by Michael S. Gutter and Selena Garrison, describes the rights that people have for insurance continuation and portability under COBRA and HIPPA, and strategies people might use for paying for unplanned health care coverage expenses. Published by the UF Department of Family Youth and Community Sciences, October 2009.